Motives of Cyberbullying Behavior by Teenage K-Pop Fans on Twitter Social Media - Widya Sandrila; Wahyunengsih Wahyunengsih (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
The current development of internet technology around the world is increasingly sophisticated, all levels of society can enjoy the benefits of this internet. The existence of social media has now become a primary need that cannot be separated from human life. The presence of increasingly diverse social media has become a place for young K-Pop fans to cyberbully on various applications, one of which is Twitter. The selection of topics in this article aims to find out the motives or reasons behind these young K-Pop fans carrying out acts of cyberbullying. In research on this topic, the author will use qualitative methods by collecting non-participatory observational data and in-depth interviews with two informants, whom the author has traced and indeed indicated to be perpetrators of cyberbullying on social media Twitter. The results of the study found that the motives of young KPOP fans to carry out cyberbullying on Twitter social media were due to the nature of fanaticism towards idols, feeling annoyed and angry when they saw posts/tweets that vilified idols, jealousy or envy of other idol fans, lack of understanding of ethics and norms -norms of behavior on social media, and feel satisfied and happy if they feel they have won the debate.